Peningkatan Kemampuan Membaca Permulaan dengan Menggunakan Media Kartu Kata Berwarna pada Siswa Kelas IA MIN 1 Kota Bengkulu - Hartati, Sri (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The objectives of this research was to know the improving teaching activity and ability of early reading by using media card coloured words on the students class IA of MIN 1 Kota Bengkulu. This research was an action research done in two cycles performed, each cycle was consist of four stages namely: planning, acting, observing, and reflecting. This research was done in class IA that consist of 30 students, 18 female students, and 12 male students. The data collected by observation sheet of the teaching activity and an oral tes of early reading. Then, the data analyzed by avarage, percentage, and classification. The results of research showed that the students’ activity in teaching early reading increased from first cycle with average 60,71 with classification “enough” became 80,21 in second cycle with classifiation “good”. Meanwhile the students’ ability of early reading also increase from first cycle with average 69,70 with classification “enough” became 80,16 in second cycle with classifiation “very good”. Based on the result of the research, it can be concluded that there were improving teaching activity and ability of early reading by using media card coloured words on the students class IA of MIN 1 Kota Bengkulu.